Glucose transporters: Important regulators of endometrial cancer therapy sensitivity - Zhang, Xing; Lu, Jia-Jing; Abudukeyoumu, Ayitila; Hou, Ding-Yu; Dong, Jing; Wu, Jiang-Nan; Liu, Li-Bing; Li, Ming-Qing; Xie, Feng (Frontiers in Oncology, 2022)
Glucose is of great importance in cancer cellular metabolism. Through working together with several glucose transporters (GLUTs), they provide enough energy for biological growth. The main glucose transporters in endometrial cancer (EC) are Class 1 (GLUTs 1-4) and Class 3 (GLUTs 6, 8), and the overexpression of theses GLUTs have been observed. Apart from providing abundant glucose uptake, these highly-expressed GLUTs also participate in the activation of many crucial signaling pathways concerning the proliferation, angiogenesis and metastasis of EC. In addition, overexpressed GLUTs may also cause endometrial cancer cells (ECCs) to be insensitive to hormone therapy or even resistant to radiotherapy and chemoradiotherapy. Therefore, GLUT inhibitors may hopefully become a sensitizer for EC precision targeted therapies. This review aims to summarize the expression regulation, function and therapy sensitivity of GLUTs in ECCs, aiming to provide a new clue for better diagnosis and treatment of EC.